The international computer and information literacy study from a European perspective: Introduction to the Special Issue. (November 2017) - Gerick, Julia; Eickelmann, Birgit; Bos, Wilfried
The International Computer and Information Literacy Study (ICILS 2013) provides, for the first time, information about students' computer and information literacy (CIL), as well as its acquisition, based on a computer-based test for students and background questionnaires. Among the 21 education systems that participated in ICILS 2013, there are 12 European countries, making secondary comparative in-depth analyses at a European level particularly fruitful. Accordingly, while the four articles in this Special Issue each deal with different topics and adopt different methodologies, they all share a common element and provide European comparisons in the ICILS context. The editorial in turn outlines the aim of the ICILS 2013 study and its relevance for European education research as well as its contextual framework and approach to the measurement of students' CIL. The potential and challenges of such large-scale assessment studies are also discussed.